The Environmental Performance of Air Conditioning Systems in Heritage Buildings in Tropical Climates - Sulaiman, Raha Binti; S.N., Kamaruzzaman; S. P., Rao; M, Pitt (Journal of Surveying, Construction and Property, 2011)
This paper examines the performance of retrofitting climate control systems focusing on air conditioning systems in refurbished old buildings in tropical climates. Data was gathered by means of investigation in the sequential steps of condition survey, space audit, ventilation systems, indoor/outdoor temperature reading and relative humidity (RH) measurement. The study raises several important issues relating to indoor environmental quality. Beyond the obvious aesthetical issues that are addressed here, the installation of air conditioning systems tends to create thermal instabilities and indoor environment imbalances in refurbished buildings. Furthermore, there is also a gap between the necessities of conserving the precious features of old buildings and the demand for better thermal comfort by the occupants. This study outlines the risks as well as making recommendations for future strategies. Keywords: Climate control, indoor environment, heritage buildings, Malaysia